A nano-adsorbent material and a method for treating landfill leachate

By using nanoadsorbent materials to treat the landfill leachate, the problems of low efficiency, high cost and secondary pollution in the prior art are solved, and efficient and economical removal of harmful substances are achieved.

CN119746811APending Publication Date: 2025-04-04MAANSHAN JIEYUAN ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411643516.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing sewage treatment technology has problems such as low efficiency, high cost, easy equipment to be blocked and secondary pollution when treating landfill leachate, making it difficult to completely remove harmful substances.

Method used

Nanoadsorption materials are used, which are composed of nanobiochar, mesoporous silica, modified zeolites, diatom mud, high-density polyethylene, quartz sand and composite microorganisms. They effectively remove harmful substances in the landfill leachate through adsorption and degradation reactions.

Benefits of technology

In the case of small usage, nanoadsorbent materials can effectively remove harmful substances in landfill leachate, which has the advantages of simple use and low operating cost, and avoids secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139111600000081
    Figure BDA0005139111600000081
Patent Text Reader

Abstract

The present invention discloses a nano-adsorbent material and a method for treating landfill leachate, and relates to the technical field of sewage treatment. The nano-adsorbent material comprises the following raw materials in mass fractions: 5-8 parts of nano-biochar, 3-6 parts of mesoporous silica, 4-5 parts of modified zeolite, 2-3 parts of diatom mud, 40-50 parts of high-density polyethylene, 2-3 parts of quartz sand, and 4-5 parts of composite microorganisms; the method for treating landfill leachate by using the nano-adsorbent material comprises the following steps: adding the nano-adsorbent material to the landfill leachate for adsorption and degradation reaction. The nano-adsorbent material of the present invention can effectively remove harmful substances in the landfill leachate when used in a small amount, and has the advantages of simple use method and low operating cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sewage treatment, and in particular to a nano-adsorption material and a method for treating landfill leachate using the nano-adsorption material. Background Art

[0002] Landfill leachate is high-concentration organic wastewater generated during the landfill process of solid waste. It mainly comes from precipitation, organic matter degradation and the inherent water in the solid waste itself. The harmful substances in it mainly include fluorine, ammonia nitrogen and heavy metal ions.

[0003] At present, the main methods for treating leachate include reinjection, biological treatment, physicochemical treatment and land treatment. Although the reinjection method reduces COD, it is an incomplete treatment method because the degradation of nitrogen-containing compounds increases the total nitrogen concentration by 30%; in anaerobic treatment, when the load increases to a certain extent, the removal rate will drop seriously; the oxidant oxidation method requires a large amount of oxidant; evaporation and distillation will cause scaling and fouling problems. Physicochemical treatment methods include membrane technology, which uses membrane components such as microfiltration, nanofiltration, ultrafiltration, and reverse osmosis to intercept pollutants in wastewater, thereby achieving the purpose of purifying water quality. However, membrane components are frequently maintained and replaced, difficult to clean, easy to clog, have large fluctuations in processing volume, and high operating costs. At the same time, the concentrated water produced by membrane treatment is difficult to treat and is prone to secondary pollution.

[0004] In view of this, it is urgent to develop a new process for treating leachate. Summary of the invention

[0005] The object of the present invention is to provide a nano-adsorbent material and a method for treating landfill leachate to solve the problems existing in the above-mentioned prior art.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A nano-adsorption material comprises the following raw materials in parts by weight: 5-8 parts of nano-biochar, 3-6 parts of mesoporous silica, 4-5 parts of modified zeolite, 2-3 parts of diatom mud, 40-50 parts of high-density polyethylene, 2-3 parts of quartz sand and 4-5 parts of composite microorganisms.

[0008] Furthermore, the composite microorganism comprises the following components in parts by weight: 5-6 parts of Rhodopseudomonas palustris, 2-3 parts of nitrifying bacteria, 1-2 parts of Pseudomonas aeruginosa, 2-3 parts of Bacillus cereus and 3-4 parts of Fusobacterium.

[0009] Furthermore, the method for preparing the nano biochar comprises the following steps:

[0010] A. Soaking the biomass powder in a mixed solution of sodium metasilicate and iron salt, ultrasonically treating and drying the mixture to obtain a biomass powder loaded with silicon and iron;

[0011] B. Placing the silicon- and iron-loaded biomass powder under an inert atmosphere for high-temperature treatment to obtain the nano biochar.

[0012] Furthermore, the biomass powder is powder obtained by crushing corn straw, wheat straw or rice straw; the iron salt includes one or more of ferric nitrate, ferric chloride, ferric sulfate, ferrous chloride and ferrous sulfate;

[0013] The concentration of sodium metasilicate in the mixed solution is 2-4 mol / L, and the concentration of iron salt is 0.2-0.5 mol / L;

[0014] The ultrasonic treatment time is 60 to 80 minutes;

[0015] The high temperature treatment is performed at a temperature of 600 to 700° C. and for a time of 2 to 3 hours.

[0016] The nano biochar can effectively adsorb metal ions in wastewater.

[0017] Furthermore, the preparation method of the mesoporous silica comprises the following steps: uniformly mixing dodecylamine solution, concentrated ammonia water, ethyl orthosilicate and water, performing a hydrothermal reaction, then collecting the precipitate, and calcining the precipitate at a high temperature to obtain the mesoporous silica.

[0018] Furthermore, the concentration of the dodecylamine solution is 0.1-0.15wt.%; the volume ratio of the dodecylamine solution, concentrated ammonia water, tetraethyl orthosilicate and water is 100:2.5:4:30;

[0019] The temperature of the hydrothermal reaction is 150-180°C and the time is 3-4h;

[0020] The high temperature calcination temperature is 450-500° C. and the time is 3-4 hours.

[0021] Furthermore, the preparation method of the modified zeolite comprises the following steps:

[0022] (1) adding natural zeolite to a sodium hydroxide solution, heating under reflux for reaction, and then washing to neutrality to obtain modified zeolite I;

[0023] (2) mixing the modified zeolite I and kaolin, adding the mixture to a succinic acid solution, stirring the mixture for reaction, and washing the mixture until the mixture is neutral to obtain the modified zeolite II;

[0024] (3) Soaking the modified zeolite II in a sodium chloride solution, stirring to react, and washing until neutral to obtain the modified zeolite.

[0025] Furthermore, in step (1), the concentration of the sodium hydroxide solution is 10 to 15 g / L; the temperature of the heating reflux reaction is 100° C., and the time is 2 to 3 h;

[0026] In step (2), the mass ratio of the modified zeolite I to kaolin is 10:3; the concentration of the succinic acid solution is 0.3-0.4 mol / L; the speed of the stirring reaction is 110-120 r / min, and the time is 3-4 h;

[0027] In step (3), the concentration of the sodium chloride solution is 2-3 mol / L; the rotation speed of the stirring reaction is 110-120 r / min, and the time is 5-6 h.

[0028] Modified zeolite can effectively adsorb fluoride ions in wastewater.

[0029] The preparation method of the nano-adsorbent material comprises the following steps:

[0030] The nano-biochar, mesoporous silica, modified zeolite, diatom mud, high-density polyethylene and quartz sand are placed in a high-speed mixer and stirred and mixed, and then sent into a twin-screw extruder for extrusion granulation to obtain nano-composite particles;

[0031] The composite microorganisms are added to a liquid culture medium for cultivation, and then the nano composite particles are added for further cultivation, and the microorganisms are attached to the surface of the nano composite particles to obtain the nano adsorption material.

[0032] Furthermore, the temperature of the extrusion granulation is 150-180°C; the particle size of the extrusion granulation is 4-6 mm;

[0033] The temperature of the continued culture is 24-28° C., and the time is 2-3 days.

[0034] Another object of the present invention is to provide a method for treating landfill leachate using the above-mentioned nano-adsorbent material, comprising the following steps:

[0035] The nanometer adsorption material is added into the landfill leachate to carry out adsorption and degradation reaction.

[0036] Beneficial effects of the present invention:

[0037] The nano-adsorption material of the present invention can effectively remove harmful substances in landfill leachate when used in a small amount, and has the advantages of simple use method, low operation cost, etc. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The Rhodopseudomonas palustris, nitrifying bacteria, Pseudomonas aeruginosa, Bacillus cereus and Fusobacterium used in the following examples of the present invention are all commercially available.

[0040] The bacterial count of Rhodopseudomonas palustris was 1.0×10 8 cfu / g, and the content of nitrifying bacteria was 2.0×10 9 cfu / g, and the bacterial count of Pseudomonas aeruginosa was 6.0×10 8 cfu / g, and the bacterial content of Bacillus cereus was 9.0×10 9 cfu / g and the bacterial count of Fusobacterium was 3.0×10 8 cfu / g.

[0041] Example 1

[0042] A method for preparing a nano-adsorbent material:

[0043] (1) The nano-adsorption material is composed of the following raw materials in parts by weight: 6 parts of nano-biochar, 6 parts of mesoporous silica, 5 parts of modified zeolite, 3 parts of diatom mud, 50 parts of high-density polyethylene, 2 parts of quartz sand and 5 parts of composite microorganisms.

[0044] The composite microorganism comprises the following components in parts by weight: 6 parts of Rhodopseudomonas palustris, 3 parts of nitrifying bacteria, 2 parts of Pseudomonas aeruginosa, 2 parts of Bacillus cereus and 4 parts of Fusobacterium.

[0045] (2) Preparation method of nano biochar:

[0046] A. Crush corn stalks to 100 mesh to obtain biomass powder.

[0047] B. The biomass powder is immersed in a mixed solution of sodium metasilicate and iron salt (the concentration of sodium metasilicate in the mixed solution is 3 mol / L, and the concentration of iron salt (ferric nitrate and ferric chloride with a molar ratio of 1:1) is 0.5 mol / L), ultrasonically treated for 60 minutes and then dried (temperature is 80°C, time is 24 hours) to obtain biomass powder loaded with silicon and iron.

[0048] C. The silicon- and iron-loaded biomass powder is placed in an inert atmosphere for high-temperature treatment (heating rate of 10°C / min, temperature of 700°C, time of 2h), and naturally cooled to room temperature to obtain nano-biochar.

[0049] (3) Preparation method of mesoporous silica

[0050] A 0.15wt.% dodecylamine solution, a 25wt.% concentrated ammonia solution, ethyl orthosilicate and water were uniformly mixed in a volume ratio of 100:2.5:4:30, and then subjected to a hydrothermal reaction (temperature of 160°C, time of 4h), centrifuged, the precipitate was collected, and the precipitate was calcined at high temperature (temperature of 500°C, time of 4h) to obtain mesoporous silica.

[0051] (4) A method for preparing a modified zeolite, comprising the following steps:

[0052] The natural zeolite was added to a sodium hydroxide solution with a concentration of 15 g / L and heated to reflux for reaction (temperature of 100°C for 2.5 h), and then allowed to stand for 24 h. The precipitate was washed to neutrality to obtain modified zeolite I.

[0053] Modified zeolite I and kaolin were mixed in a mass ratio of 10:3 and added into a 0.3 mol / L succinic acid solution, stirred for reaction (speed of 120 r / min, time of 4 h), then allowed to stand for 24 h, and the precipitate was washed to neutrality to obtain modified zeolite II;

[0054] The modified zeolite II was immersed in a sodium chloride solution with a concentration of 3 mol / L, stirred for reaction (rotation speed of 110 r / min, time of 6 h), and then allowed to stand for 24 h, and the precipitate was washed to neutrality to obtain the modified zeolite.

[0055] (5) Preparation method of nano-adsorbent material:

[0056] Nano-biochar, mesoporous silica, modified zeolite, diatom mud, high-density polyethylene and quartz sand were placed in a high-speed mixer and stirred and mixed, and then sent to a twin-screw extruder for extrusion granulation (granulation temperature was 180° C., and particle size was 4 mm) to obtain nano-composite particles;

[0057] Five parts of composite microorganisms were added to 100 parts of LB liquid culture medium and cultured for 24 hours (temperature was 26°C) to obtain a mixed bacterial solution. Nanocomposite particles were added to the mixed bacterial solution and cultured for 3 days (temperature was 26°C). The mixture was filtered and dried at low temperature (40°C) to obtain a nano-adsorbent material.

[0058] Example 2

[0059] A method for preparing a nano-adsorbent material:

[0060] (1) The nano-adsorption material is composed of the following raw materials in parts by weight: 8 parts of nano-biochar, 3 parts of mesoporous silica, 4 parts of modified zeolite, 3 parts of diatom mud, 40 parts of high-density polyethylene, 3 parts of quartz sand and 4 parts of composite microorganisms.

[0061] The composite microorganism comprises the following components in parts by weight: 5 parts of Rhodopseudomonas palustris, 2 parts of nitrifying bacteria, 2 parts of Pseudomonas aeruginosa, 2 parts of Bacillus cereus and 3 parts of Fusobacterium.

[0062] (2) Preparation method of nano biochar:

[0063] A. Crush rice straw to 100 mesh to obtain biomass powder.

[0064] B. Soak the biomass powder in a mixed solution of sodium metasilicate and iron salt (the concentration of sodium metasilicate in the mixed solution is 2 mol / L, and the concentration of iron salt (ferric nitrate and ferrous chloride with a molar ratio of 1:1) is 0.3 mol / L), ultrasonically treat for 80 minutes and then dry (temperature is 80°C, time is 24 hours) to obtain biomass powder loaded with silicon and iron.

[0065] C. The silicon- and iron-loaded biomass powder is placed in an inert atmosphere for high-temperature treatment (heating rate of 10°C / min, temperature of 700°C, time of 3h), and naturally cooled to room temperature to obtain nano-biochar.

[0066] (3) Preparation method of mesoporous silica

[0067] A 0.1wt.% dodecylamine solution, a 25wt.% concentrated ammonia solution, ethyl orthosilicate and water were uniformly mixed in a volume ratio of 100:2.5:4:30, and then subjected to a hydrothermal reaction (temperature of 150°C, time of 3h), centrifuged, the precipitate was collected, and the precipitate was calcined at high temperature (temperature of 450°C, time of 4h) to obtain mesoporous silica.

[0068] (4) A method for preparing a modified zeolite, comprising the following steps:

[0069] The natural zeolite was added to a sodium hydroxide solution with a concentration of 12 g / L and heated under reflux for reaction (temperature of 100°C for 2 h), and then allowed to stand for 24 h, and the precipitate was washed to neutrality to obtain modified zeolite I;

[0070] Modified zeolite I and kaolin were mixed in a mass ratio of 10:3 and added into a 0.4 mol / L succinic acid solution, stirred for reaction (speed of 110 r / min, time of 3 h), then allowed to stand for 24 h, and the precipitate was washed to neutrality to obtain modified zeolite II;

[0071] The modified zeolite II was immersed in a sodium chloride solution with a concentration of 2 mol / L, stirred for reaction (rotation speed of 120 r / min, time of 5 h), and then allowed to stand for 24 h, and the precipitate was washed to neutrality to obtain the modified zeolite.

[0072] (5) Preparation method of nano-adsorbent material:

[0073] Nano-biochar, mesoporous silica, modified zeolite, diatom mud, high-density polyethylene and quartz sand were placed in a high-speed mixer and stirred and mixed, and then sent to a twin-screw extruder for extrusion granulation (the granulation temperature was 150° C. and the particle size was 6 mm) to obtain nano-composite particles;

[0074] Five parts of composite microorganisms were added to 100 parts of LB liquid culture medium and cultured for 24 hours (temperature was 24°C) to obtain a mixed bacterial solution. Nanocomposite particles were added to the mixed bacterial solution and cultured for 2 days (temperature was 24°C), filtered and dried at low temperature (40°C) to obtain nano adsorption materials.

[0075] Comparative Example 1

[0076] The same as Example 1, except that the nano biochar is replaced with an equal mass fraction of mesoporous silica.

[0077] Comparative Example 2

[0078] Same as Example 1, except that the nano biochar is replaced with an equal mass fraction of modified zeolite.

[0079] Comparative Example 3

[0080] The same as Example 1, except that the modified zeolite is replaced with diatom mud of equal mass fraction.

[0081] Example 4

[0082] A method for treating landfill leachate:

[0083] 20 g of the nano-adsorption materials prepared in the example and the comparative example were added to 1 L of landfill leachate (before treatment) respectively, and the adsorption and degradation reactions were carried out for 72 hours.

[0084] The contents of fluoride ions, ammonia nitrogen and heavy metal ions in the landfill leachate were determined. The results are shown in Table 1.

[0085] Table 1

[0086]

[0087] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A nano-adsorbent material, characterized in that: The invention comprises the following raw materials in parts by weight: 5-8 parts of nano biochar, 3-6 parts of mesoporous silica, 4-5 parts of modified zeolite, 2-3 parts of diatom mud, 40-50 parts of high-density polyethylene, 2-3 parts of quartz sand and 4-5 parts of composite microorganisms.

2. A nano-adsorbent material according to claim 1, characterized in that: The composite microorganism comprises the following components in parts by weight: 5-6 parts of Rhodopseudomonas palustris, 2-3 parts of nitrifying bacteria, 1-2 parts of Pseudomonas aeruginosa, 2-3 parts of Bacillus cereus and 3-4 parts of Fusobacterium.

3. The nano-adsorbent material according to claim 1, characterized in that: The method for preparing the nano biochar comprises the following steps: A. Soaking the biomass powder in a mixed solution of sodium metasilicate and iron salt, ultrasonically treating and drying the mixture to obtain a biomass powder loaded with silicon and iron; B. Placing the silicon- and iron-loaded biomass powder under an inert atmosphere for high-temperature treatment to obtain the nano biochar.

4. A nano-adsorbent material according to claim 3, characterized in that: The biomass powder is powder obtained by crushing corn straw, wheat straw or rice straw; the iron salt includes one or more of ferric nitrate, ferric chloride, ferric sulfate, ferrous chloride and ferrous sulfate; The concentration of sodium metasilicate in the mixed solution is 2-4 mol / L, and the concentration of iron salt is 0.2-0.5 mol / L; The ultrasonic treatment time is 60 to 80 minutes; The high temperature treatment is performed at a temperature of 600 to 700° C. and for a time of 2 to 3 hours.

5. The nano-adsorbent material according to claim 1, characterized in that: The preparation method of mesoporous silica comprises the following steps: uniformly mixing dodecylamine solution, concentrated ammonia water, ethyl orthosilicate and water, performing hydrothermal reaction, collecting precipitates, and calcining the precipitates at high temperature to obtain the mesoporous silica.

6. A nano-adsorbent material according to claim 5, characterized in that: The concentration of the dodecylamine solution is 0.1-0.15 wt.%; the volume ratio of the dodecylamine solution, concentrated ammonia water, tetraethyl orthosilicate and water is 100:2.5:4:30; The temperature of the hydrothermal reaction is 150-180°C and the time is 3-4h; The high temperature calcination temperature is 450-500° C. and the time is 3-4 hours.

7. The nano-adsorbent material according to claim 1, characterized in that: The preparation method of the modified zeolite comprises the following steps: (1) adding natural zeolite to a sodium hydroxide solution, heating under reflux for reaction, and then washing to neutrality to obtain modified zeolite I; (2) mixing the modified zeolite I and kaolin, adding the mixture to a succinic acid solution, stirring the mixture for reaction, and washing the mixture until the mixture is neutral to obtain the modified zeolite II; (3) Soaking the modified zeolite II in a sodium chloride solution, stirring to react, and washing until neutral to obtain the modified zeolite.

8. The nano-adsorbent material according to claim 7, characterized in that: In step (1), the concentration of the sodium hydroxide solution is 10-15 g / L; the temperature of the heating reflux reaction is 100° C., and the time is 2-3 h; In step (2), the mass ratio of the modified zeolite I to kaolin is 10:3; the concentration of the succinic acid solution is 0.3-0.4 mol / L; the speed of the stirring reaction is 110-120 r / min, and the time is 3-4 h; In step (3), the concentration of the sodium chloride solution is 2-3 mol / L; the rotation speed of the stirring reaction is 110-120 r / min, and the time is 5-6 h.

9. The nano-adsorbent material according to claim 1, characterized in that: The preparation method of the nano-adsorbent material comprises the following steps: The nano-biochar, mesoporous silica, modified zeolite, diatom mud, high-density polyethylene and quartz sand are placed in a high-speed mixer and stirred and mixed, and then sent into a twin-screw extruder for extrusion granulation to obtain nano-composite particles; The composite microorganisms are added to a liquid culture medium for cultivation, and then the nano composite particles are added for further cultivation, and the microorganisms are attached to the surface of the nano composite particles to obtain the nano adsorption material.

10. A method for treating landfill leachate using the nano-adsorbent material according to any one of claims 1 to 9, characterized in that: The following steps are involved: The nanometer adsorption material is added into the landfill leachate to carry out adsorption and degradation reaction.